The fibrin/fibrinogen degradation product level on arrival in trauma patients is a better predictor of a fatal outcome than physiological or anatomical severity: A retrospective chart review. (January 2022) - Nagasawa, Hiroki; Omori, Kazuhiko; Nojiri, Shuko; Muramatsu, Ken-Ichi; Kushida, Yoshihiro; Takeuchi, Ikuto; Jitsuiki, Kei; Shitara, Jun; Ohsaka, Hiromichi; Oode, Yasumasa; Yanagawa, Youichi
Aim: We performed a retrospective investigation to determine the factors, including vital signs, severity of traumatic anatomical abnormality and biochemical data, which are most useful for predicting the outcomes of trauma patients after admission. Methods: A retrospective medical chart review was performed for all trauma patients who were admitted to our department from September 2017 to August 2019. These subjects were then divided into two groups according to whether they survived to hospital discharge or not. Results: During the investigation period, 790 patients were enrolled as subjects (Death group, n = 34; survival group, n = 756). The injury severity score, serum glucose level, prothrombin time, international normalized ratio and fibrin/fibrinogen degradation product level in the Death group were significantly greater than those in the Survival group. A multivariate analysis showed that the fibrin/fibrinogen degradation product level was a significant predictor of a fatal outcome (odds ratio 1.00, 95% confidence interval 1.0008-1.0040, p value = 0.0008). Conclusions: The fibrin/fibrinogen degradation product levels on arrival may be a better predictor of a fatal outcome in trauma patients than physiological or anatomical severity.